Failure analysis of cemented carbide roller for cold rolling: Material characterisation, numerical analysis, and material modelling. (October 2020) - Lanzutti, A.; Srnec Novak, J.; De Bona, F.; Bearzi, D.; Magnan, M.; Fedrizzi, L.
Highlights: Failure analysis of a cemented carbide roller used for cold rolling was performed. A material failure analysis was combined with an FE analysis. The roller failed due to rolling fatigue in proximity to a material internal pore. The FE analysis indicated that the roller failed in the region with the highest multiaxial stress. The component failed because the fatigue limit was reached. Abstract: Cemented carbides, also known as hard metals (HM), are composite materials that are widely used in many technological applications requiring favourable mechanical properties, specifically a high wear resistance. In the steelmaking industry, these materials have been effectively used to produce rollers for both hot and cold rolling operations. In this study, failure analysis of a roller used for cold rolling was performed, starting from a detailed material investigation to a fracture surface characterisation using scanning electron microscopy with energy-dispersive X-ray spectroscopy (SEM + EDXS). A finite element (FE) analysis of the roller was performed to determine the Hertzian-type stress distribution in the contact area. To identify the most critical zone, the Crossland multiaxial criterion was applied, and the results were then compared with measurements obtained from a component failure analysis. An additional investigation of the possible causes of failure was performed by adopting a material model (the Murakami–Endo equation) to distinguish the actual causes of failure more clearly, mainly at the crack nucleation site. The failure analysis results showed that the roller failed primarily because of rolling fatigue, which started from an internal pore acting as a source of local stress concentration. The component reached the fatigue limit of the material in proximity to the pore, which behaved as a crack nucleation site.